Advances in imaging and electron physics. - Hawkes, P. W. (Advances in imaging and electron physics ;, 2004)
The series bridges the gap between academic researchers and R & D designers by addressing and solving daily issues, which makes it essential reading. This volume looks at theory and it's application in a practical sense, with a full account of the methods used and realistic detailed application. The authors do this by examining the latest developments, historic illustrations and mathematical fundamentals of the exciting developments in imaging and electron physics and apply them to realistic practical situations. * Emphasizes broad and in depth article collaborations between world-renowned scientists in the field of image and electron physics * Presents theory and it's application in a practical sense, providing long awaited solutions and new findings * Provides the steps in finding answers for the highly debated questions.